Hydrogen production via supercritical water gasification of almond shell over algal and agricultural hydrochars as catalysts - Safari, Farid; Javani, Nader; Yumurtaci, Zehra (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
Almond shell is one of the most abundant agricultural wastes in Kurdistan province of Iran. Conversion of almond shell into hydrogen-rich gas via supercritical water gasification (SCWG) was investigated in this study using a tubular batch micro-reactor system. Non catalytic tests were carried out in different conditions to determine the optimum condition for H-2 production. Maximum hydrogen yield of 7.85 mmoVg, was observed in the temperature of 460 degrees C, residence time (RT) of 10 min and feed/water ratio (F/W) of 0.01. Catalytic experiments were performed using hydrochars as solid residues remained after SCWG of Cladophora glomerata (C. glomerata) macroalgae and wheat straw. Hydrochars were characterized by ICP-OES, FESEM and BET methods. For catalytic experiments, hydrochars were added to the almond shell by the weight ratio of 0.4. Conversion of almond shell and hydrogen production, were more influenced by the presence of inorganic compounds in the hydrochars rather than the surface area and pore volume. The maximum hydrogen yields of 10.77 and 11.63 mmoVg, were observed for catalytic experiments in the presence of wheat straw and C. glomerata hydrochars, respectively. (C) 2017 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Supercritical water; Gasification; Almond shell; Hydrochar; Catalyse; HYDROTHERMAL GASIFICATION; RICH GAS; CLADOPHORA-GLOMERATA; BIOMASS; MACROALGAE; BIOCHAR; NICKEL; Chemistry; Electrochemistry; Energy & Fuels